Evaluation of Phytochemical Composition of Extractives and Proximate Analysis of Tagetes minuta Powdered Leaves and Flowers - Opondo, Florence Atieno; K’Owino, Isaac Odhiambo; Chepkwony, Sarah Cherono; Kosgei, Viola Jepchumba (European Journal of Applied Sciences, 2023)
Tagetes minuta is an invasive plant in agricultural areas. However, the weed has found application in herbal tea and as feed additive in industrial applications. Commercial poultry feeds on the other hand are costly and synthetic antibiotics are always added to the feeds to increase the production and growth rate through reduced disease incidence. However, this unnecessary use of antibiotic feed additives in poultry feed is associated with development of antibiotic-resistant bacteria and increased risk of occurrence of antibiotics residues in human beings. Hence, valorization of T. minuta into feed additive is envisaged to be a readily available, ecofriendly and sustainable alternative. The aim of this study therefore was to screen the secondary metabolites present, determine the phytochemical composition and perform the proximate analysis of nutrients present in powders from T. minuta leaves and flowers. Extraction was performed using maceration method with ethanol as solvent followed by the phytochemical screening of the extractives using standard qualitative methods. Determination of total phenolic content (TPC) and total tannin content (TTC) in the extractives followed the Folin-Ciocalteu method while total flavonoid content (TFC) was evaluated using the aluminum chloride colorimetric method. The proximate analysis study was done using the Association of official analytical chemists (AOAC) methods to evaluate moisture content, ash, crude fiber, crude protein, lipid content, and carbohydrate content. Phytochemical screening revealed the presence of phenols, flavonoids, alkaloids, tannins, saponins, glycosides, steroids and terpenoids in the ethanolic extracts of T. minuta, while the phytonutrients assayed in the powdered material were carbohydrates, lipids, and proteins. During proximate analysis it was observed that powdered leaves of T. minuta contained 8.463 ± 0.23 % moisture, total ash of 5.709 ± 0.22 %, and dry matter of 91.537 ± 0.30 % as compared to 12.285 ± 0.29 % moisture, total ash 8.794 ± 0.15 %, and dry matter of 87.715 ± 0.27 % observed in the flowers. Analysis of nutritive composition revealed that lipid content (28.167 ± 0.24 %), crude protein (12.194 ± 0.08 %) and carbohydrate content (14.088 ± 0.11 %), was high in the leaves as compared to 23.824 ± 0.32 % lipid content, 9.750 ± 0.15 % crude protein, and 11.317 ± 0.12 % carbohydrate content, observed in the flowers. Based on these findings, the current study affirms that powdered leaves and flowers of T. minuta contain phytochemicals and phytonutrients which could be valorized into phytogenic poultry feed additive.